Is Black-Scholes Model An Appropriate Option Pricing Tool in Chinese Stock Market? - Mao, Qing (2007)
In order to further develop the derivative markets, the Chinese government has decided to launch stock options as soon as possible. The Black-Scholes formula has been the most commonly used option pricing model today. But is the Black-Scholes model an appropriate tool for pricing of Chinese stock option?